1996
DOI: 10.1177/088610999601100304
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes and Stigma: What's Changed for Welfare Mothers

Abstract: In the debate on welfare reform, stereotypes of women on welfare have resurfaced, and most proposals for reform are designed to modify and regulate women's behaviors. This article, based on information obtained in focus groups of recipients of Aid to Families with Dependent Children, examines how women manage the stigma of being welfare mothers and what they think about "cheating" the system. The most striking difference between recipients of the 1990s and of the 1960s is the belief of current recipients that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 7 publications
1
35
1
Order By: Relevance
“…Thus, their children struggle not just economically but in other aspects of life as well. Additionally, the findings from the AWSP are consistent with the literature on single mothers who receive welfare, which suggests that the economic status of a mother is related to the perceived quality of parenting she provides (Davis & Hagen, 1996;Jarrett, 1994Jarrett, , 1996McCormack, 2004).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Thus, their children struggle not just economically but in other aspects of life as well. Additionally, the findings from the AWSP are consistent with the literature on single mothers who receive welfare, which suggests that the economic status of a mother is related to the perceived quality of parenting she provides (Davis & Hagen, 1996;Jarrett, 1994Jarrett, , 1996McCormack, 2004).…”
Section: Discussionsupporting
confidence: 78%
“…If these negative attitudes indeed exist, it is necessary to examine them because research has shown that individuals who internalize stigmas associated with negative societal views are more likely to feel shame, which may lead to psychological distress (Furåker & Blomsterberg, 2003;Schmader, Johns, & Forbes, 2008). More specific to the current study, negative societal views have been shown to lead to a sense of hopelessness, depression, shame, and low selfesteem among custodial single mothers (Davis & Hagen, 1996). Furthermore,…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…The element that distinguishes their perceptions from those of recipients interviewed in other recent studies (Davis & Hagen, 1996;Nelson, 2002;Seccombe & Battle-Walters, 1998;Tickameyer, 2000) is their use of race to understand their perceptions of problematic interactions within the system that administers welfare benei'its. As was found in the studies noted, women in this study were well aware of the negative popular images of welfare recipients and of the stigma associated with receipt of the benefit.…”
Section: Discussionmentioning
confidence: 99%
“…They characterized their own use of the benefit, however, as necessary to make ends meet during a period of difficulty, typically brought on by a lack of supports such as childcare or assistance from their children's fathers. Another study found that recipients justified their use of welfare as a stepping stone while engaging in education or other measures to improve their lives (Davis & Hagen, 1996). Again, women tried to distance themselves from the stereotypical welfare cheat.…”
Section: Literature Review Race Welfare and Prejudicementioning
confidence: 99%